2014
DOI: 10.1002/jcb.24863
|View full text |Cite
|
Sign up to set email alerts
|

Tension Force‐Induced ATP Promotes Osteogenesis Through P2X7 Receptor in Osteoblasts

Abstract: Orthodontic tooth movement induces alveolar bone resorption and formation by mechanical stimuli. Force exerted on the traction side promotes bone formation. Adenosine triphosphate (ATP) is one of the key mediators that respond to bone cells by mechanical stimuli. However, the effect of tension force (TF)-induced ATP on osteogenesis is inadequately understood. Accordingly, we investigated the effect of TF on ATP production and osteogenesis in MC3T3-E1 cells. Cells were incubated in the presence or absence of P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 53 publications
4
44
0
Order By: Relevance
“…ALPase hydrolyzes ester bonds in organic phosphate compounds under alkaline conditions and plays an important role in bone calcification [34]. Previous our study showed that a one of the mechanical stimuli tension force affects ALPase activity in mineralization of osteoblasts [35]. In this study, we observed that LIPUS enhanced ECM protein expression and increased phosphate concentration and calcium content in the ECM and that A438079 blocked these LIPUS effects.…”
Section: Discussionsupporting
confidence: 51%
“…ALPase hydrolyzes ester bonds in organic phosphate compounds under alkaline conditions and plays an important role in bone calcification [34]. Previous our study showed that a one of the mechanical stimuli tension force affects ALPase activity in mineralization of osteoblasts [35]. In this study, we observed that LIPUS enhanced ECM protein expression and increased phosphate concentration and calcium content in the ECM and that A438079 blocked these LIPUS effects.…”
Section: Discussionsupporting
confidence: 51%
“…Both are activated by ATP, which is involved in osteogenic differentiation, and promote mineralization. Indeed, the activation of P2X7, via ATP or by an agonist, has been shown to induce ALP and cbfa1/runx2 expression by HBMSCs (Kariya et al, ). Moreover, adenine nucleotides have been shown to stimulate bone formation by increasing the expression of osteoblast‐related genes, such as Cbfa1/Runx2 (Ciciarello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The most popular commercially available units are Flexcell International Cooperation (Burlington, NC). Flexcell provides uniform radial and circumferential strain on cells cultured on flexible membranes . Although the loading of this platform might not fully represent the physiological situation, various studies were conducted based on this platform to investigate tendon cell behavior under 2D biaxial loading (Table S2).…”
Section: Loading Model For Tendon Mechanobiologymentioning
confidence: 99%
“…Flexcell provides uniform radial and circumferential strain on cells cultured on flexible membranes. 63 Although the loading of this platform might not fully represent the physiological situation, various studies were conducted based on this platform to investigate tendon cell behavior under 2D biaxial loading (Table S2). Loading regimes used in these studies are within the range of 2-12% tension and 0.25-2 Hz.…”
Section: D In Vitro Loading Modelmentioning
confidence: 99%